A Needs Analysis for Developing a STEM-R Module on Renewable Energy to Foster MTs Students' Creative Thinking - Mega Kurnia; Ismet; Hamdi Akhsan (Universitas Nurul Huda, 2026)
In the context of 21st-century education, students are required to master a range of skills, one of which is creative thinking. This study conducted a needs analysis to guide the development of STEM-R-based teaching modules on the topic of renewable energy. Using a descriptive qualitative approach, data were collected through document analysis (the Ministry of Religious Affairs’ vision and mission, the curriculum, and textbooks) as well as semi-structured interviews with education stakeholders. The results reveal a significant gap: although the Ministry of Religious Affairs’ vision emphasises holistic education and religious character, existing science teaching materials have not explicitly integrated Islamic values. The religious dimension (R) is entirely absent from the topic of renewable energy, even though stakeholders consistently emphasise the urgency of madrasah-specific teaching materials that contextualise science from an Islamic perspective. This study concludes that a STEM-R module on the topic of renewable energy is urgently needed. These findings indicate both the need for and potential direction of module development, which could serve as a basis for the design of future teaching materials to align with the Ministry of Religious Affairs’ educational philosophy.